2014
DOI: 10.1073/pnas.1405362111
|View full text |Cite
|
Sign up to set email alerts
|

Nedd9 restrains renal cystogenesis in Pkd1 −/− mice

Abstract: Significance This study uses mouse models for the first time to our knowledge to identify that NEDD9, a nonenzymatic scaffolding protein that is commonly amplified in cancer, has an important restraining function for the development of renal cysts in autosomal dominant polycystic kidney disease (ADPKD). In the absence of NEDD9, failure to activate Aurora-A kinase causes multiple abnormalities in cilia, intensifying the effect of genetic deficiency of mutations in the polycystic kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 45 publications
7
43
0
Order By: Relevance
“…found that genetically induced loss of cilia in mice ameliorated cystogenesis induced by defects in either Pkd1 or Pkd2 [165]. This finding was corroborated by another study, in which administration of a drug that stabilized cilia by inhibiting the cilia disassembly-promoting kinase Aurora-A exacerbated cystogenesis caused by a mutant Pkd1 [157]. These findings suggest that significant differences might exist in the aetiology and signaling dependency of cysts originating from loss of cilia and those induced by mutation of the polycystins.…”
Section: Adpkd Beyond the Hallmarks Of Cancermentioning
confidence: 76%
See 2 more Smart Citations
“…found that genetically induced loss of cilia in mice ameliorated cystogenesis induced by defects in either Pkd1 or Pkd2 [165]. This finding was corroborated by another study, in which administration of a drug that stabilized cilia by inhibiting the cilia disassembly-promoting kinase Aurora-A exacerbated cystogenesis caused by a mutant Pkd1 [157]. These findings suggest that significant differences might exist in the aetiology and signaling dependency of cysts originating from loss of cilia and those induced by mutation of the polycystins.…”
Section: Adpkd Beyond the Hallmarks Of Cancermentioning
confidence: 76%
“…Some evidence suggests that the polycystin 1 and proteins associated with its function regulate cell migration in cancer [156] and in normal development [98]; how these processes are affected in the context of ADPKD requires further study. Proteins involved in interaction with the ECM and interpretation of ECM signals for growth, including integrins, the prometastatic protein Nedd9, and their effector, Src, are upregulated with cystogenesis, and some preclinical studies targeting these proteins suggests efficacy in reducing cyst growth [43, 44, 157, 158]. …”
Section: Adpkd and The Hallmarks Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activities of NEDD9 in ADPKD reflect of its activation of the Aurora-A kinase, which induces resorption of cilia, limiting this defective signaling (Fig. 4) [104]. In addition, several recent studies implicate NEDD9 and Aurora-A with regulation by and regulation of calcium/calmodulin signaling, not only in ciliary signaling, but also in control of mitosis, which may inform the oncogenic activity of NEDD9 and Aurora-A [105107].…”
Section: Nedd9 In Other Human Pathological Conditionsmentioning
confidence: 99%
“…While a thorough review is premature because insufficient numbers of molecular variants have been identified and functionally characterized, current evidence suggests considerable heterogeneity in the types of sequence variation that produce modifier effects. The studies discussed in this review provide examples of modifier variants that cause partial or complete loss of gene function (e.g., missense mutation 32,66 or gene deletion 33,40 ), enhanced function (e.g., increased protein stability 30 ), and gain of alternative function (e.g., novel protein-protein interaction 75 ). They also demonstrate that modifier variants often occur within protein-coding exons, but may alternatively affect regulatory regions such as UTRs or promoters.…”
Section: Features Of Modifier Genes Nature Of Sequence Variationmentioning
confidence: 99%